2013
DOI: 10.1002/ccd.25270
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery duplex ultrasound criteria for the detection of significant in‐stent restenosis

Abstract: Duplex ultrasonography is an accurate technique to identify significant restenosis in stented renal arteries. The PSV and RAR cutoffs for detecting renal artery ISR are higher than those in native, unstented renal arteries. A normal duplex ultrasound after renal artery stenting virtually excludes significant restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…Chi et al [18], in a study of 67 patients with renal artery stents, found that a PSV of at least 395 cm/s or RAR of at least 5.1 was most predictive of significant in-stent stenosis. Similarly, Del Conde et al [19], in a study of 132 stented renal arteries, reported a mean PSV of 382 cm/s and RAR of 5.3 in arteries with >60% stenosis.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 75%
“…Chi et al [18], in a study of 67 patients with renal artery stents, found that a PSV of at least 395 cm/s or RAR of at least 5.1 was most predictive of significant in-stent stenosis. Similarly, Del Conde et al [19], in a study of 132 stented renal arteries, reported a mean PSV of 382 cm/s and RAR of 5.3 in arteries with >60% stenosis.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 75%
“…A periodic follow‐up duplex ultrasound is an accurate non‐invasive screening tool to detect ISR of renal stents . We could not perform a follow‐up renal arterial Doppler in case 4, as he was lost to follow up for some time.…”
Section: Discussionmentioning
confidence: 99%
“…They studied 67 patients stented for renal artery stenosis and compared them with 55 nonstented patients and determined that a PSV >395 cm/s or RAR >5.1 were most predictive of instent restenosis >70%. Lastly, Del Conde et al, 16 in 2014, established another set of velocity parameters to detect renal artery in-stent restenosis. A PSV <240 cm/s excluded significant in-stent restenosis (negative predictive value, 96%), a PSV $296 cm/s or RAR >4.4 was highly accurate for $60% stenosis (positive predictive value, 94% and 96%, respectively), and a PSV in the range of 241 to 296 cm/s indicated a "gray zone" that warranted further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] The reported experience suggests that velocities in widely patent renal arteries with bare-metal stents tend to be higher than those in widely patent native renal arteries and that the use of velocity thresholds for stenosis in native renal arteries will overestimate the incidence of significant in-stent restenosis. 7,10,11,13,16 This difference has also been reported for native vs stented carotid arteries. [17][18][19][20] Some authors have attributed this observation to decreased arterial compliance in stented arteries.…”
mentioning
confidence: 99%